Activated carbons from the co-pyrolysis of rice wastes for Cr(III) removal - Dias, Diogo (2018)
ABSTRACT: Rice husk and polyethylene were mixed (50 % w/w each) and submitted to a pyrolysis assay. Four physical activations with CO2 were performed on the resulting co-pyrolysis char (PC). The activation at 800 °C, for 4h, generated the activated carbon (PAC3) with the best textural properties. PC, PAC3 and a commercial activated carbon (CAC) were characterized and submitted to Cr(III) removal assays. PC had a high percentage of volatile matter that was removed after the physical activation, resulting in more available pores in the final material (PAC). In the Cr(III) removal assays, two S/L ratios were tested: 5 and 10 g L-1. PC did not remove any Cr(III) from the solutions, but PAC presented similar results to CAC. At the S/L of 5 g L-1, Cr(III) removal was of 58.5 % for PAC and 62.5 % for CAC, both by adsorption mechanism; at the S/L of 10 g L-1, Cr(III) removal was almost complete due to precipitation caused by pH increase. The highest uptake capacities were of 7.92 mg g-1 for PAC and 8.71 mg g-1 for CAC, at the S/L of 5 g L-1. The results indicated that PAC3 may be a viable alternative to CAC on Cr(III) removal from aqueous media.